Peran Albumin Glikat Pada Kontrol Glikemik dan Diagnosis Diabetes Mellitus - Sharlene Sabrina; Putu Ristyaning Ayu; Iswandi Darwis (Medula, 2019)
Diabetes Mellitus or DM is a chronic metabolic syndrome, which is usually characterized by excess glycemic conditions or hyperglycemia. The incidence of diabetes is increasing rapidly in populations in Asia, especially in countries with fairly fast economic growth. At present, there are around 171-194 million people in the world who suffer from diabetes. Fructosamine, glycated albumin and HbA1c are glycate proteins used to evaluate glycemic control in diabetic patients. Albumin glycate (GA) has a much shorter half-life than erythrocytes, so glycemic albumin can reflect glycemic control on a short-term basis (around 2-3 weeks) compared to HbA1c. In addition, GA has faster and greater changes compared to HbA1c, so GA may be more useful for describing glycemic control. The concentration of albumin glycate can be determined in several ways, namely by using the colorimetric method with thiobarbituric acid, the enzymatic method with proteinase and ketamine oxidase, the HPLC chromatography method, and the mass spectrometry method. Several studies have concluded that there is a strong relationship between glycated albumin, HbA1c and fasting blood glucose so that glycated albumin can be used as a glycemic control tool for early detection of diabetes complications, aiding diagnosis of diabetes and assisting in the selection of adequate management for diabetes patients.